(untitled) - Allen, Robert (London, 2004)
Revised and updated for its second edition with new definitions and the latest buzzwords, The Penguin Dictionary is the most accessible single-volume dictionary available. The Penguin Dictionary offers a complete guide to the English language. As well as clear, detailed definitions, there are usage notes on difficult aspects of grammar and words that are often confused; there are short encyclopedia entries on concepts such as freedom, consciousness and structualism written by leading commentators in their fields.
Keywords: English language,Tiếng Anh; Dictionaries,Từ điển